2022
DOI: 10.3390/ani12192638
|View full text |Cite
|
Sign up to set email alerts
|

Differential Spleen miRNA Expression Profile of Beagle Dogs Infected with Toxocara canis

Abstract: Toxocara canis is an unnoticed zoonotic helminth that causes severe disease in animals and humans. The spleen has a wide range of immunological functions in protecting the host against infection by many pathogens, but the function of the spleen in T. canis infection is still to be clarified, especially for the role of spleen microRNAs (miRNAs). In this study, deep sequencing of spleen RNA samples of 18 Beagle puppies was conducted to uncover the miRNAs expression profiling at 24 h post-infection (hpi), 96 hpi,… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
1
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
2

Relationship

0
2

Authors

Journals

citations
Cited by 2 publications
(1 citation statement)
references
References 56 publications
(59 reference statements)
0
1
0
Order By: Relevance
“…In the 2 of 13 study of parasites, miRNAs interact with the host and the parasite to influence processes such as immune regulation and gene regulation in vivo [8]. Many studies have shown that parasitic infections cause alterations in the host miRNA expression profile [9]. A cryptosporidium infection causes changes in the miRNA expression profile in host epithelial cells [10].…”
Section: Introductionmentioning
confidence: 99%
“…In the 2 of 13 study of parasites, miRNAs interact with the host and the parasite to influence processes such as immune regulation and gene regulation in vivo [8]. Many studies have shown that parasitic infections cause alterations in the host miRNA expression profile [9]. A cryptosporidium infection causes changes in the miRNA expression profile in host epithelial cells [10].…”
Section: Introductionmentioning
confidence: 99%